2010
DOI: 10.1007/s10526-010-9321-y
|View full text |Cite
|
Sign up to set email alerts
|

Do acoustic cues mediate host finding by Syngaster lepidus (Hymenoptera: Braconidae)?

Abstract: Syngaster lepidus Brullé is a braconid solitary ectoparasitoid that attacks the larvae of the cerambycid beetles Phoracantha semipunctata and Phoracantha recurva. The beetle larvae are concealed under the bark of their Eucalyptus host trees feeding at the interface of the inner bark and the wood. Ovipositing female parasitoids search the bark surface and must first locate a host larva accurately, drill through as much as 1 cm of the bark in order to paralyze the larva beneath, and lay a single egg on the paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…This inability to regulate high larval densities was also exhibited by the same braconid wasps in a previous study attacking P. semipunctata in E. globulus Labillardière and E. obliqua L'Héritier logs in eastern Australia (Hanks et al 2001). This response appears to depend on factors altering wasp effectiveness in finding larval hosts which may include use of volatiles to locate borer infested hosts (Johnson et al 2016), acoustic cues and audible mechanisms suggested to be used by wasps to find P. semipunctata larvae feeding on the phloem/sapwood (Joyce et al 2011), surface vibrations from borer larvae feeding (Godfray 1994) as was suggested to be used by these braconid wasps when attacking P. semipunctata (Hanks et al 2001), and intensive searching by other braconid wasps (Richerson & Borden 1972). Also, the increased choice of borer infested hosts, combined with the habit of these wasps to land on logs arbitrarily, rather than to remain in one place (Driessen & Bernstein 1999), may have meant that the braconid wasps were likely dispersing throughout the clearfell site and had moved away from host logs with high neonate densities, rather than increasing their chances of finding more individuals among a few logs.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…This inability to regulate high larval densities was also exhibited by the same braconid wasps in a previous study attacking P. semipunctata in E. globulus Labillardière and E. obliqua L'Héritier logs in eastern Australia (Hanks et al 2001). This response appears to depend on factors altering wasp effectiveness in finding larval hosts which may include use of volatiles to locate borer infested hosts (Johnson et al 2016), acoustic cues and audible mechanisms suggested to be used by wasps to find P. semipunctata larvae feeding on the phloem/sapwood (Joyce et al 2011), surface vibrations from borer larvae feeding (Godfray 1994) as was suggested to be used by these braconid wasps when attacking P. semipunctata (Hanks et al 2001), and intensive searching by other braconid wasps (Richerson & Borden 1972). Also, the increased choice of borer infested hosts, combined with the habit of these wasps to land on logs arbitrarily, rather than to remain in one place (Driessen & Bernstein 1999), may have meant that the braconid wasps were likely dispersing throughout the clearfell site and had moved away from host logs with high neonate densities, rather than increasing their chances of finding more individuals among a few logs.…”
Section: Discussionmentioning
confidence: 52%
“…2016), acoustic cues and audible mechanisms suggested to be used by wasps to find P. semipunctata larvae feeding on the phloem/sapwood (Joyce et al . 2011), surface vibrations from borer larvae feeding (Godfray 1994) as was suggested to be used by these braconid wasps when attacking P. semipunctata (Hanks et al . 2001), and intensive searching by other braconid wasps (Richerson & Borden 1972).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intense selection pressure on parasitoids to locate hosts is well illustrated by the variety of cues and strategies used in host searching (Wang et al , 2010; Joyce et al , 2011; Benelli et al , 2013 b , c ; Colazza et al , 2013; Uefune et al , 2013). The stimuli sources used by parasitoids may be direct, as the host itself, or indirect, as the microhabitat of the host or a cue associated with its activity (Vet & Dicke, 1992; Steidle & van Loon, 2003; Colazza et al , 2013; Uefune et al , 2013).…”
Section: Introductionmentioning
confidence: 99%